ANALISIS KETEPATAN KODE DIAGNOSIS KASUS PERSALINAN PADA PASIEN RAWAT INAP DI RUMAH SAKIT DKT SIDOARJO TAHUN 2022 - Annisa Safitri Azzahro; Chyntia Vicky Alvionita (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
The implementation of coding in labor cases at DKT Sidoarjo Hospital still has inaccuracies of 61.73%, while the accuracy of medical records is 38.27%. The accuracy and inaccuracy of disease diagnosis coding will affect data and information in the health service process and reduce the quality of service in the hospital. The purpose of this study was to analyze the accuracy of the diagnosis code for labor cases in inpatients at DKT Sidoarjo Hospital. This type of research uses quantitative and qualitative methods, with data collection in the form of observation and interviews. The number of samples used was 81 medical records in July–November 2022 cases of childbirth in inpatients, and the number of informants was 1 person who was a key informant. In this study, the accuracy of the results of the maternal complication component was obtained with 55.56% accuracy, the method of delivery with 61.73% accuracy, and the outcome of delivery with 67.90% accuracy. Then the total results were obtained with 38.27% accuracy. The results of the interview found that the accuracy of coding can be influenced by the 5M factors (man, method, material, machine, and money). Conclusion: Most of the diagnosis codes in labor cases are incorrect. So the coding officer should be more careful in coding, both regarding the rules and procedures for coding diagnoses based on ICD-10.